COVID19 Pandemic and the Binational Couples - Japur, Ana Carolina de Souza Medeiros (Universidade Estadual Paulista (Unesp), 2020)
In this episode of the Foreign Language Learner Podcast, a student in the second year of Translation Studies at Unesp - São José do Rio Preto talks about living in the Covid19 pandemic. What is more important than having the people we love by our side during these terrible times? A movement that has spread all around the world is helping binational couples get together again!
Nível de proficiência de produção oral autoavaliado pelo aluno: C2
Keywords: COVID19 Pandemic; English language Pronunciation by foreigners; COVID-19; Pandemias; Língua inglesa Pronúncia estrangeira